Middle Class Evolving To Precariat: Labour Conditions for the 21st Century - Andoni Alonso; Sílvia Ferreira; David Alonso (Social Work and Society, 2016)
Middle Class has become a confusing term. Low, medium and high middle classes are attempts to reorganize meaning. The appearance of new middle classes in emergent countries adds new difficulties to make sense of the concept. This is the reason why some authors disqualify the very notion of middle class. This paper tries to articulate the appearance of a new social class, the precariat that absorbs part of the falling members of middle class and working class in general. It is proposed also to revise two basic concepts concerning middle classes: the public good and consumerism in order to give political content for this concept. Public should be transformed into commons and de-growth should be a guideline for future political action.